Dinâmica espacial e temporal da AIDS em Fortaleza, Ceará - Pedrosa, Nathália Lima (2015)
AIDS manifests itself unevenly in different spaces. Geographic Information Systems are effective resources to identify priority areas that require control measures. This study aimed to characterize AIDS in Fortaleza, to perform spatial and temporal distribution of its and to identify spatial clusters. Ecological study, focusing on spatial analysis. The study locus was Fortaleza, capital of Ceará, with the unit of analysis the neighborhood. Secondary data were obtained from the AIDS reporting forms from 2002 to 2013 and population data from the Instituto Brasileiro de Geografia e Estatística. Characterized population with AIDS in terms of gender, race, age, sexual orientation and injecting drug use. The spatial distribution and temporal incidence occurred in three periods, from the crude incidence, standardized, general Global Bayesian and Local Bayesian and crude and standardized incidence by sex and age group. It analyzed the spatial autocorrelation by the Moran index. MoranMap was a resource of visualization and analysis of the distribution of the disease. 5,807 cases aged over 13 years and living in Fortaleza were diagnosed with AIDS. There was a increase of standardized incidence (p=0.038), with linear trend (R² = 0.36). It consist of mostly male (p=0.022), with trend line rising (R² = 0.43) and ratio of sexes were stable. The average of age 40-49 years present incidence´s mean of 7.8 cases/100.000 inhabitants, the highest incidence and it´s statistically significant (p <0.001). The proportion of cases 13-19 years for females (41.5%) was statistically significant (p = 0.015). Most cases are brown, with filling improvement in this regard over time. The majority sexuality was heterosexual (60.8%), worsening the quality of information of that variable. Use of injectable drugs (1.3%) had mostly male (81.5%), with statistical significance for the age group 25-29 years and 45-49 years. There was a positive spatial autocorrelation in the incidence of age group 30-34 years in the first period, 13-19 years in the last period and female in the last period. Crude and standardized incidence had increased range of focus variation and identified neighborhoods "silent". The incidence of Local Bayesian allowed better visualization of clusters of rates. Over time, there was "movement" of AIDS clusters for the western portion of the city, marked by poverty, as well as constant clusters on the northern coast, tourist region of the city. Clusters of rates of AIDS in male sex can be found on the north coast portion and female in the poorest neighborhoods economically. The neighborhoods Messejana, Praia de Iracema, Centro, Arraial Moura Brasil, Jacarecanga, Farias Brito, Benfica, Cajazeiras, Barroso, Damas, Couto Fernandes, Montese, Jockey Clube and João XXIII present higher rates incidence AIDS throughout the period. AIDS is a growing epidemic in the city and is distributed unevenly, requiring public health actions in the clusters targeted as the specificities of the population living in those neighborhoods.